2020
DOI: 10.15405/epsbs.2020.03.187
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Influencer Marketing On The Global Economy

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They try to persuade individuals to take advice, possibly even modify behaviours, by the information they produce, as well as their expertise, abilities, and character (Dajah, 2020;L. Liu et al, 2022;Vyatkina, 2020) According to marketing research, when a person's activities are consistent with their independent, self-reliant, authentic selves, people are more likely to see them as genuine (such as a celebrity) (Kostygina et al, 2020;Taillon et al, 2020). Celebrities who are viewed as genuine have more power over others, both online and offline (Jiang & Yin, 2021;Sokolova & Perez, 2021).…”
Section: The Application Of Self-determination Theory Towards Healthy...mentioning
confidence: 99%
“…They try to persuade individuals to take advice, possibly even modify behaviours, by the information they produce, as well as their expertise, abilities, and character (Dajah, 2020;L. Liu et al, 2022;Vyatkina, 2020) According to marketing research, when a person's activities are consistent with their independent, self-reliant, authentic selves, people are more likely to see them as genuine (such as a celebrity) (Kostygina et al, 2020;Taillon et al, 2020). Celebrities who are viewed as genuine have more power over others, both online and offline (Jiang & Yin, 2021;Sokolova & Perez, 2021).…”
Section: The Application Of Self-determination Theory Towards Healthy...mentioning
confidence: 99%
“…Macro influencers are followed by 100.000-1.000.000 subscribers, and micro-influencers have 1000 to 100.000 followers. Nano influencers are appealed to less than 1000 followers (Vyatkina, 2020).…”
Section: Vloggersmentioning
confidence: 99%
“…If the companies know how to decide the right influencer, they can successfully organize their campaigns and run the promotions. Vyatkina (2020) concludes that influencer marketing has impacted many numbers of brands. Moreover, it is shown that the usage of influencers provides a great reach of a brand due to the already built connection and trust between the influencers and their followers.…”
Section: Vloggersmentioning
confidence: 99%